The hope for hysteresis in foreign aid - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2006)
We argue that a purpose of foreign aid is to whet the appetite of the recipient in order to bring about a long term commitment to what the donor perceives as a need, but which the recipient may rank lower down on his list of undertakings, or may be sufficiently resource constrained as to be unable to start the project. In other words, we explore the implications and conditions for success of a donor trying to affect long-term recipient policy by creating path dependence. Once the project is established, aid can be removed without reversing the process that has been set in motion. Quite simply, the donor wants its project to stick. We place a formal structure on this.
Keywords: O10; O19; F35; O11; C23; O47; E21; E22; 330; Foreign aid; rent seeking; governance; decentralization